2002
DOI: 10.1075/wll.5.1.05rag
|View full text |Cite
|
Sign up to set email alerts
|

Verbal structure and content in written discourse

Abstract: This paper forms a bridge between the article on noun phrase patterning by Ravid et al. 2002 and that on passive voice constructions by Jisa et al. 2002. The study reports on a cross-linguistic, developmental study of verbal structures and verb types used in two genres of written discourse: personal narratives and expository texts. The study is aimed at (a) establishing the profile of linguistic features that characterize and differentiate these two genres; (b) identifying the developmental changes beyond midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
2
4
0
4
Order By: Relevance
“…Expository texts are mostly written in the (timeless) present tense. These findings correspond to those of Ragnarsdóttir et al (2002), who compared the form and content of verb phrases in narrative and expository texts written by hearing children and adults in five languages. Moreover, our data showed that typically developing hearing individuals at all age levels had no difficulties with temporal reference marking.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Expository texts are mostly written in the (timeless) present tense. These findings correspond to those of Ragnarsdóttir et al (2002), who compared the form and content of verb phrases in narrative and expository texts written by hearing children and adults in five languages. Moreover, our data showed that typically developing hearing individuals at all age levels had no difficulties with temporal reference marking.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Group interacted with Age ( F (4,128) = 3.19, p < .05, η 2 p = .09) and with Tense ( F (4,156) = 4.82 p < .01, η 2 p = .07). As can be seen in Table 3, all nine groups of writers clearly anchor their expository texts in the present tense (as also observed in a cross-linguistic study on hearing writers who wrote expository texts in one of five different languages; Ragnarsdóttir et al, 2002). At a more detailed level, however, the pattern in the 11–12-year-old proficient signers is somewhat different.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…This is the case of argument structure that differs across cultures (Uysal, 2012): How arguments are linked in argumentative texts differs and involves different sentence structures or connectors. Similarly, regarding text genres, Ragnarsdóttir, Aparici, Cahana‐Amitay, van Hell, and Viguié (2002) showed that cross‐linguistic similarities and differences about typological structures of verbs used in five languages allowed for differentiating text genres. Therefore, higher order writing skills are also dependent, presumably to a lesser extent than lexical and syntactic proficiencies, on the linguistic contexts, such as information structure and the inherent lexical properties of arguments (Duguine, Huidobro, & Madariaga, 2010; Witzlack‐Makarevich & Seržant, 2018).…”
Section: Writing Research Across Languagesmentioning
confidence: 97%